2009
DOI: 10.1128/aem.01002-09
|View full text |Cite
|
Sign up to set email alerts
|

Use of Inorganic and Organic Nitrogen by Synechococcus spp. and Diatoms on the West Florida Shelf as Measured Using Stable Isotope Probing

Abstract: The marine nitrogen (N) cycle is a complex network of biological transformations in different N pools. The linkages among these different reservoirs are often poorly understood. Traditional methods for measuring N uptake rely on bulk community properties and cannot provide taxonomic information.15 N-based stable isotope probing (SIP), however, is a technique that allows detection of uptake of individual N sources by specific microorganisms. In this study we used 15 N SIP methodology to assess the use of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 55 publications
2
57
0
Order By: Relevance
“…Additionally, as shown by PCA analysis, it is possible that DON released from dust particles played an auxiliary role in stimulating cyanobacteria, in the first response phase. This is not suprising since there is evidence that cyanobacteria can assimilate some small labile components of DON (Zubkov et al, 2003;Wawrik et al, 2009). DIN seemed to accumulate after the first two experimental days (Figure 1) mostly influencing the larger phytoplankton cells in the second response phase as shown by PCA analysis.…”
Section: Discussion the Effect Of Dust Addition Treatments On Phytoplmentioning
confidence: 99%
“…Additionally, as shown by PCA analysis, it is possible that DON released from dust particles played an auxiliary role in stimulating cyanobacteria, in the first response phase. This is not suprising since there is evidence that cyanobacteria can assimilate some small labile components of DON (Zubkov et al, 2003;Wawrik et al, 2009). DIN seemed to accumulate after the first two experimental days (Figure 1) mostly influencing the larger phytoplankton cells in the second response phase as shown by PCA analysis.…”
Section: Discussion the Effect Of Dust Addition Treatments On Phytoplmentioning
confidence: 99%
“…Prochlorococcus growth has traditionally been considered to be based mainly on regenerated forms of nitrogen (Moore et al , 2007, though they are also known to assimilate nitrate (Casey et al 2007, Martiny et al 2009, Treibergs et al 2014. Synechococcus are able to use a large diversity of new and regenerated forms of nitrogen, including nitrate, nitrite, ammonium, urea and amino acids (Glibert et al 1986, Wawrik et al 2009). They can even degrade their own phycoerythrin to use as an internal nitrogen source under extreme nitrogendepleted conditions (Wyman et al 1985).…”
Section: Control Of Nutrient Supply On Picoplanktonmentioning
confidence: 99%
“…ISSN 2164-7682 2015 www.macrothink.org/emsd 106 TN had the strongest linear relationship with chlorophyll-a and cyanobacterial cell counts, with the particulate and dissolved organic fraction driving the strength of the relationship, indicating that nutrients have been incorporated into cyanobacterial growth or were recycling as dissolved organic forms within the water column. Other studies have found significant relationships between CyanoHABs and organic nitrogen sources, such as DON and urea, that are utilized by phytoplankton, and stimulate cyanobacterial growth (Kudela et al 2008;Wawrik et al 2009;Altman and Paerl 2012). The significant correlations between cyanobacterial cell counts, TN, and chlorophyll-a suggest that a primary target for management and mitigation strategies should be reduction in nutrient loading.…”
Section: Discussionmentioning
confidence: 95%